Finding the "True" N0 Cohort: Technical Aspects of Near-infrared Sentinel Lymph Node Mapping in Non-small Cell Lung Cancer. Issue 4 (October 2020) - Phillips, William W.; Weiss, Kathleen D.; Digesu, Christopher S.; Gill, Ritu R.; Mazzola, Emanuele; Tsukada, Hisashi; Schumacher, Lana Y.; Colson, Yolonda L.
Abstract : Objective: To examine technical-, patient-, tumor-, and treatment-related factors associated with NIR guided SLN identification. Background: Missed nodal disease correlates with recurrence in early stage NSCLC. NIR-guided SLN mapping may improve staging and outcomes through identification of occult nodal disease. Methods: Retrospective analysis of 2 phase I clinical trials investigating NIR-guided SLN mapping utilizing ICG in patients with surgically resectable NSCLC. Results: In total, 66 patients underwent NIR-guided SLN mapping and lymphadenectomy after peritumoral ICG injection. There was significantly increased likelihood of SLN identification with injection dose ≥1 mg compared to <1 mg (65.2% vs 35.0%, P = 0.05), lung ventilation after injection (65.2% vs 35.0%, P = 0.05), and albumin dissolvent (68.1%) compared to fresh frozen plasma (28.6%) and sterile water (20.0%) ( P = 0.01). In patients receiving the optimized ICG injection, there was significantly increased likelihood of SLN identification with radiologically solid nodules compared to sub-solid nodules (77.4% vs 33.3%, P = 0.04) and anatomic resection compared to wedge resection (88.2% vs 52.2%, P = 0.04). Disease-free and overall survival are 100% in those with a histologically negative SLN identified (n = 25) compared to 73.6% ( P = 0.02) and 63.6% ( P = 0.01) in patients with node negative NSCLC established via routine lymphadenectomy alone (n = 22). Conclusions: SLN(s) are more reliably identified with ICG dose ≥1 mg, albumin dissolvent, post-injection lung ventilation, radiologically solid nodules, and anatomic resections. To date, N0 status when established via NIR SLN mapping seems to be associated with decreased recurrence and improved survival after surgery for NSCLC.